2020
DOI: 10.26717/bjstr.2020.24.004035
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Pesticides Residues in Eggplant and Tomatoes from Central Marked in Khartoum State Using Quechers Method and Gas Liquid Chromatography-Mass Spectrometry

Abstract: A pesticide defines as "any substance or mixture of substances intended for preventing, destroying, attracting, repelling, or controlling any pest including unwanted species of plants or animals during the production, storage, transport, distribution, and processing of food, agricultural commodities, or animal feeds or which may be administered to animals for the control of ectoparasites, pesticides are part of a large group of organic compounds that present extremely diverse physico-chemical properties and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The prevalence of pesticide contamination of vegetables in our study is comparable with pesticide residue prevalence reported in vegetables elsewhere in Sub-Saharan Africa: 46% in Tanzania (Kapeleka et al, 2020) and 54% in Kenya (Nakhungu et al, 2017), with higher values sometimes reported: 63% in Zambia (Mwanja et al, 2017), 92% in Sudan (Ali et al, 2020) and 96% in Tanzania (Mahugija et al, 2017). However, in Ethiopia, pesticide residues in vegetables has seldom been assessed (Loha et al, 2020), with a few studies assessing the residues in other commodities such as khat (Daba et al, 2011;Atnafie et al, 2021), wheat (Daba et al, 2011) and tea (Siraj et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence of pesticide contamination of vegetables in our study is comparable with pesticide residue prevalence reported in vegetables elsewhere in Sub-Saharan Africa: 46% in Tanzania (Kapeleka et al, 2020) and 54% in Kenya (Nakhungu et al, 2017), with higher values sometimes reported: 63% in Zambia (Mwanja et al, 2017), 92% in Sudan (Ali et al, 2020) and 96% in Tanzania (Mahugija et al, 2017). However, in Ethiopia, pesticide residues in vegetables has seldom been assessed (Loha et al, 2020), with a few studies assessing the residues in other commodities such as khat (Daba et al, 2011;Atnafie et al, 2021), wheat (Daba et al, 2011) and tea (Siraj et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Monitoring of pesticide residue concentrations in vegetables should be performed routinely to assess MRL compliance and protect consumers. Demonstrable effective monitoring can also help build trust between exporting and importing countries by showing oversight and control of food safety (Mahugija et al, 2017;Ali et al, 2020;Omwenga et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have developed MRMs using the QuEChERS method to analyze various pesticides [ 22 , 23 , 24 ]; however, for such MRMs to be utilized in the Republic of Korea, these methods must be validated for foods frequently consumed by Koreans [ 25 , 26 , 27 , 28 , 29 ]. In 2019, the government of the Republic of Korea introduced the Positive List System (PLS), which applies a uniform MRL criterion (0.01 mg/kg) to all imported agricultural products for which a specific MRL has not been established in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Since its adoption as an Association of Official Analytical Chem (AOAC) method in 2003, the recently improved QuEChERS method has been appr as an official method of analysis in a number of European countries (EN 15662 met (Figure 1) [21]. Several previous studies have developed MRMs using the QuEChERS method t alyze various pesticides [22][23][24]; however, for such MRMs to be utilized in the Repub Several previous studies have developed MRMs using the QuEChERS method to analyze various pesticides [22][23][24]; however, for such MRMs to be utilized in the Republic of Korea, these methods must be validated for foods frequently consumed by Koreans [25][26][27][28][29]. In 2019, the government of the Republic of Korea introduced the Positive List System (PLS), which applies a uniform MRL criterion (0.01 mg/kg) to all imported agricultural products for which a specific MRL has not been established in Korea.…”
Section: Introductionmentioning
confidence: 99%